Auditory brainstem response with cognitive interference in normal and autism spectrum disorder children - understanding the auditory sensory gating mechanism - Dzulkarnain, Ahmad Aidil Arafat; Sulaiman, Nur Hafizah; Shahrudin, Fatin Amira; Sidek, Shahrul Na'im; Md Yusof, Hazlina; Khalid, Madihah (IntechOpen, 2022)
Earlier studies disputed the influence of higher-order function such as attention or cognitive inhibition on the auditory brainstem response (ABR) result. In short, the ABR result was considered similar with or without the subject paying attention. However, in the last few years, there has been growing evidence that the higher-order function may influence the ABR findings provided the sensory gating system of the brain is triggered by any cognitive interference activities. This chapter will explain the concept of auditory sensory gating, a method to measure auditory sensory gating, and at the end of the chapter, preliminary findings concerning the ABR with cognitive interference among ten normally developing children are presented. This chapter will also share a case study that compared auditory sensory gating capacity in normal and children with mild autism spectrum disorder (ASD).